1986
DOI: 10.3109/00016348609155170
|View full text |Cite
|
Sign up to set email alerts
|

Conization by Carbon Dioxide Laser or Cold Knife in the Treatment of Cervical Intra‐Epithelial Neoplasia

Abstract: In a randomized trial concerning 123 women with CIN, 59 were treated with laser conization under colposcope without further hemostatic remedy and 64 with cold knife conization guided by Schiller's iodine dyeing supported by side sutures, vaginal packing and postoperative oral administration of tranexam acid. Follow-up with colposcopy and cytology was done 3 and 12 weeks post-conization and then every 6 months. The average follow-up period was 36 months (28-48). Peroperative bleeding was rather less pronounced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0
4

Year Published

1993
1993
2013
2013

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 8 publications
(10 reference statements)
2
31
0
4
Order By: Relevance
“…Allocation-Concealment of allocation was satisfactory in 11 trials (Alvarez 1994;Cherchi 2002;Chirenje 2001;Crompton 1994;Dey 2002;Giacalone 1999;Gilbert 1989;Healey 1996;Oyesanya 1993;Panoskaltsis 2004a;Partington 1989) but was not reported in any of the other 18 trials.…”
Section: Risk Of Bias In Included Studiesmentioning
confidence: 96%
See 4 more Smart Citations
“…Allocation-Concealment of allocation was satisfactory in 11 trials (Alvarez 1994;Cherchi 2002;Chirenje 2001;Crompton 1994;Dey 2002;Giacalone 1999;Gilbert 1989;Healey 1996;Oyesanya 1993;Panoskaltsis 2004a;Partington 1989) but was not reported in any of the other 18 trials.…”
Section: Risk Of Bias In Included Studiesmentioning
confidence: 96%
“…Primary haemorrhage: Meta-analysis of two trials (Bostofte 1986;Kristensen 1990), assessing 316 participants, found no statistically significant difference between laser conisation and knife conisation in the risk of primary haemorrhage (RR 0.53, 95% CI 0.18 to 1.54). The percentage of the variability in effect estimates that was due to heterogeneity rather than by chance may represent moderate heterogeneity (I 2 = 40%).…”
Section: Laser Conisation Compared With Knife Conisationmentioning
confidence: 99%
See 3 more Smart Citations